312 Intermittent Hypoxia: Effects on Brain Stem of Oxidative Stress and NRF2 Transcription Factor Activation in a Rat Pup Model. (October 2012) - Vento, M
Abstract : Background: Apnea of prematurity is a common condition in the neonatal period caused by immature brainstem respiratory neural output. Apneic episodes and resultant intermittent hypoxia are a potential cause of oxidative stress during this vulnerable developmental period. Objective: We tested the hypothesis that chronic intermittent hypoxia alters oxidative metabolism and resultant redox status in the medulla of rat pups. Design/methods: Litters of 10 rat pups and their dams were assigned to one of two groups: normoxia (controls) and intermittent hypoxia (Hx). Exposure occurred from postnatal day 1 for 7 days. Chronic intermittent hypoxia consisted of exposing rat pups and their dams to alternating cycles of nitrogen (N2 ) and room air (RA): 45 seconds of hypoxia (nadir of 5% O2 ) was administered every 5 minutes for 8 hours/day. For controls, animals were kept at RA. On the eighth day, brainstems were harvested and quickly snap frozen in liquid nitrogen. Reduced (GSH) and oxidized (GSSG) glutathione, and the GSH precursors -glutamyl-cysteine (-G-cysteine) and L-cysteine in medulla were determined by UPLC-MS/MS. Malondialdehyde (MDA) in medulla was determined by HPLC. Results: Reduced glutathione (GSH) was significantly reduced in the brainstem of rat pups submitted to chronic intermittent hypoxic episodes associated with reduction in GSH/GSSG ratio. GSH precursors, -glutamyl-cysteine and L-cysteine were also significantly lower in the brainstem of intermittent hypoxia group.